Surviving race, ethnicity, and nationality : a challenge for the twenty-first century - Gracia, Jorge J. E. (Rowman & Littlefield, 2005)
"Surviving Race, Ethnicity and Nationality is the first book to explore philosophically the concepts of race, ethnicity, and nationality and to offer a systematic and unified theory emphasizing metaphysical and epistemological issues. Gracia argues for a familial, historical view of ethnicity and race in the tradition of Du Bois and for a political view of nationality, the roots of which can be traced to the French Enlightenment. Meticulous criticism of Appiah on race, Corlett on ethnicity, and Miller on nationality sets the stage for the presentation of Gracia's own analytically precise discussion. Surviving Race, Ethnicity, and Nationality is an indispensable resource for anyone interested in the distinctive ways that philosophy informs and clarifies our common understanding of these complex concepts."--Jacket